Introduction: what is alumni? / Arith Syakir Bunsu ... [et al.] - Bunsu, Arith Syakir; Daniel, Nur Zafika; Ramsa, Rizwanshah; -, Siti Nur Syazwanie; Empang Wan, Veronica (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
Former students who attended or graduated in some way from a school, college, or university are known as alumni. For groupings of women, the feminine plural alumnae is occasionally used. The Latin term translates to "one who is (or has been) fed." One can be an alumni without graduating; the word is not identical with that word. The phrase is occasionally used to describe a former worker or member of an organization, a donor, or a convict.